On the nature of cracks and voids in nuclear graphite. (July 2016) - Freeman, H.M.; Jones, A.N.; Ward, M.B.; Hage, F.S.; Tzelepi, N.; Ramasse, Q.M.; Scott, A.J.; Brydson, R.M.D.
Abstract: Microcracks in neutron-irradiated nuclear grade graphite have been examined in detail for the first time using a combination of transmission electron microscopy (TEM), electron energy loss spectroscopy (EELS), energy dispersive X-ray (EDX), and energy filtered TEM (EFTEM). Filler particles from both unirradiated Pile Grade A (PGA) and three irradiated British Experimental Pile 'O' (BEPO) graphite specimens were investigated with received doses ranging from 0.4 to 1.44 displacements per atom (dpa) and an irradiation temperature of between 20 and 120 °C. We suggest that the concentration and potentially the size of microcracks increase with increasing neutron irradiation and show that disordered carbon material is present in a range of microcracks (of varying size and shape) in all specimens including unirradiated material. EFTEM and EELS data showed that these cracks contained carbon material of lower density and graphitic character than that of the surrounding bulk graphite. The presence of partially filled microcracks has potentially significant implications for the development of microstructural models for the prediction of radiation-induced dimensional and property changes in nuclear graphite.